Consentement libre et éclairé et les stérilisations imposées de femmes des Premières Nations et Inuit au Québec - Commission de la santé et des services sociaux des Premières Nations du Québec et du Labrador; Basile, Suzie; Bouchard, Patricia (2022)
La présente recherche vise à pallier le manque de données sur la stérilisation imposée de femmes des Premières Nations et Inuit au Québec. Il s’agit d’une occasion unique pour les femmes des Premières Nations et Inuit au Québec de faire connaître leur histoire et de témoigner dans un cadre respectueux des principes de recherche avec les peuples autochtones (Asselin et Basile, 2012). À notre connaissance, aucune étude n’a encore été menée sur le sujet au Québec, si bien que ce projet semble tout à fait inédit et permet de répondre à un réel besoin de faire avancer la recherche sur cette problématique. Dans cette intention, la recherche sur la stérilisation imposée des femmes des Premières Nations et Inuit permet de mettre en lumière les enjeux sous-jacents de cette problématique. Ainsi, la notion de consentement libre et éclairé est au coeur de la recherche, tout comme l’étude du racisme et de la discrimination systémique vécue par les femmes autochtones au sein du système de santé.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; intersectionnalité; justice reproductive; maternité; pol4102; premier cycle; périodes historiques; québec; recherche avec les peuples autochtones; régions géographiques; santé; sciences humaines; sciences sociales; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

Better stories for a gender equal and fairer social recovery from outbreaks: learnings from the RESISTIRÉ project - Strid, Sofia; Schrodi, Colette; Cibin, Roberto (Gender & Development, 2022)
La pandémie a radicalement modifié l’organisation de la société, avec une augmentation du travail à domicile, de l’enseignement à domicile et de la présence en ligne, le tout avec des implications spécifiques (non)intentionnelles sur le travail de soins rémunéré et non rémunéré. Ces implications, comme celles d’autres crises, sont sexistes et se manifestent selon le sexe, l’âge, le handicap, l’origine ethnique/la race, le statut migratoire, la religion, la classe sociale et les intersections entre ces inégalités. Si de nombreuses études ont identifié ces impacts inégaux et négatifs et soulignent d’importantes inégalités liées aux soins, la contribution spécifique de cet article est différente, à savoir celle de mettre en évidence des pratiques inspirantes comme de meilleures histoires de et dans le domaine des soins pendant la pandémie. L’objectif est de rendre ces meilleures histoires visibles et de les considérer comme des moyens d’atténuer les impacts inégaux de la COVID-19 et de ses réponses politiques. Théoriquement, l’approche est basée sur les « meilleures histoires », telles que développées par Dina Georgis (2013, Better Story. Queer Affects from the Middle East , New York : State University). L'article utilise des données quantitatives et qualitatives, recueillies auprès des 27 États membres de l'UE, de l'Islande, de la Serbie, de la Turquie et du Royaume-Uni, dans le cadre du projet européen H2020 RESISTIRÉ.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; covid-19; europe; intersectionnalité; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail du care

Les images de sensibilisation à la violence conjugale produites au Québec entre 1995 et 2021 : critique féministe de stratégies visuelles multiples - Yelle, Thérèse (Université du Québec à Montréal, 2022)
Dans ce projet, j’ai visé à (1) recenser les stratégies visuelles employées dans les campagnes de sensibilisation à la violence conjugale produites au Québec et à (2) établir les liens que ces stratégies entretiennent avec l'engagement féministe pris par le Gouvernement dans son Plan d'action gouvernemental en matière de violence conjugale de 1995. Dans un premier temps, à travers une étude visuelle multidisciplinaire, ancrée entre autres dans la rhétorique de l’image de Barthes (1964), mais aussi dans les théories du langage cinématographique (Edgar-Hunt, Rawle et Marland, 2011) et de l’art hypermédiatique (Lalonde, 2012), j’ai été amenée à constater la récurrence de stratégies visuelles visant à susciter des émotions fortes, comme la surprise, le choc, la colère ou la peur. Dans un deuxième temps, tout comme plusieurs auteur.trices de ma revue de littérature (West, 2013, Neal, 2015, Gabler, 2016, Goehring et al., 2017, Magaraggia et Cherubini, 2017, Wolf, 2018), j’ai remis en question la pertinence de ces stratégies dans le cadre d’une approche féministe de la violence conjugale. Pour ce faire, je me suis appuyée sur mon cadre théorique : les principes d’intervention féministes en violence conjugale. Il s’est dès lors avéré que beaucoup des images recensées contredisaient ces principes. Elles tendaient à retirer de l’agentivité aux victimes, à les revictimiser ou même à les culpabiliser. Je postule que cet état des lieux peut s’expliquer par le contexte sociopolitique et économique québécois des trente dernières années, contexte où les perspectives féministes n’ont jamais cessé d’être remises en question (Dupuis-Déri et Blais, 2015, Dupuis-Déri et Lamoureux, 2015) et où le néolibéralisme a mené à l’individualisation des problématiques sociales – entre autres (Flynn et al., 2018). Bien que ma recherche comporte ses limites, notamment car mon corpus exclut les nombreuses initiatives locales qui ont été créées, elle offre les bases d’un questionnement pertinent sur l’éthique de la fabrique des images de sensibilisation à la violence conjugale. Dans un travail ultérieur, la recherche pourrait comparer les initiatives gouvernementales aux initiatives locales, ou les initiatives du Gouvernement québécois aux initiatives d’autres gouvernements, comme celui d’Australie (campagne Respect). Il serait aussi pertinent de se questionner sur la place de ces images de sensibilisation dans un paysage médiatique et visuel où le sexisme ordinaire et les propos réactionnaires pullulent encore, malgré les avancées des dernières décennies (Cordelier et al., 2015, Lacasse et Charron, 2017). _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : image publicitaire; campagnes de sensibilisation; violence conjugale; images de la violence conjugale; lecture féministe de la violence conjugale; critique féministe de l’image; féminismes au Québec; antiféminismes au Québec.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; amériques; antiféminisme; approches et analyses; arts; biblioFem*; corps; discipline; genre; histoire de l'art; intersectionnalité; masculinisme; militance; mémoires/thèses; périodes historiques; québec; représentations médiatiques; ressource en ligne; régions géographiques; santé; thématiques; violences; violences conjugales

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Social vulnerability and the impact of policy responses to COVID‐19 on disabled people - Mladenov, Teodor; Brennan, Ciara Siobhan (Sociology of Health & Illness, 2021)
In this paper, we propose a conceptual framework for understanding the impact of the policy responses to COVID-19 on disabled people. These responses have overwhelmingly focused on individual vulnerability, which has been used as a justification for removing or restricting rights. This suggests the need to shift the attention towards the social determinants of disabled people's vulnerability. We do this by bringing literature on social vulnerability in disaster risk management or 'disaster studies' in contact with key concepts in disability studies such as the social model of disability, independent living, intersectionality, and biopower. Empirically, we draw on the findings of the global COVID-19 Disability Rights Monitor (www.covid-drm.org), as well as on reports from academic journals, civil society publications, and internet blogs. We put the proposed conceptual framework to work by developing a critical analysis of COVID-19 policies in three interrelated areas-institutional treatment and confinement of disabled people, intersectional harms, and access to health care. Our conclusion links this analysis with strategies to address disabled people's social vulnerability in post-pandemic reconstruction efforts. We make a case for policies that address the social, economic, and environmental conditions that disproportionately expose disabled people to natural disasters and hazards.
Keywords: approches et analyses; capacitisme; corps; covid-19; discipline; intersectionnalité; ressource en ligne; santé; sciences humaines; sociologie; soins de santé; systèmes d'oppressions; thématiques; vulnérabilité

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences

Femmes et Environnement. Enjeux d'égalité pour toutes les femmes - Boivin, Martine (Le Réseau des Tables régionales de groupes de femmes du Québec, 2020)
Le Réseau des Tables régionales de groupes de femmes du Québec est un regroupement provincial composé des 17 Tables régionales de groupes de femmes au Québec. Il s’agit d’un regroupement féministe de défense collective des droits, qui travaille sur les questions mettant en jeu les intérêts et les droits des femmes. La spécificité du regroupement est représentée par l’expertise régionale développée par les Tables régionales dans les dossiers de la condition féminine. Porte-voix des régions auprès des instances nationales, le RTRGFQ favorise la prise de parole collective des Tables régionales, tout en respectant leurs particularités. Le RTRGFQ et les Tables régionales sont en action depuis plus de 20 ans pour favoriser la participation des femmes à la vie démocratique québécoise
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; charge mentale; charge émotionnelle; environnement; intersectionnalité; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Genre, féminismes et développement: une trilogie en construction - Levy, Charmain; Martinez, Andrea (Collection "Études en développement international et mondialisation.", 2019)
Cet ouvrage pédagogique multidisciplinaire conçu pour les cours de premier cycle présente les principaux enjeux théoriques et pratiques de l'heure en matière de genre, féminismes et développement. Misant sur la capacité d'agir et le pouvoir de transformation sociale des femmes des Suds, ce livre examine les enjeux du genre et du développement. Ce manuel féministe, clair et facile à consulter, est spécifiquement conçu pour les cours de premier cycle universitaire sur les femmes, le genre et le développement international. Organisé en sept sections, il offre un panorama aussi vaste que possible des préoccupations féministes reliées au genre et au développement, alimentant ainsi les réflexions et les études de cas dans le domaine. Issu du colloque « État des lieux sur les perspectives féministes en développement international » du Congrès international des recherches féministes dans la francophonie (CIRFF), l'ouvrage propose des contributions de professeures-chercheuses et de militantes européennes, canadiennes et des Suds dédiées à l'avancement des connaissances féministes, à leur diffusion plus large et à leur vulgarisation. Publié en français
Keywords: afro-féminisme; approches et analyses; care; corps; cours; discipline; droits des femmes*; féminisme décolonial; féminisme postcolonial; histoire et politique; intersectionnalité; justice reproductive; outils; ouvrages de références; pol4022; premier cycle; ressource en ligne; santé; science politique; science politique et droit; thématiques; travail; violences; violences sexistes et sexuelles

“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Promouvoir des programmes d'éducation à la sexualité positive, inclusive et émancipatrice: méta-analyse qualitative intersectionnelle des besoins exprimés par les jeunes - Descheneaux, Julie; Fédération du Québec pour le Planning des naissances; Pagé, Geneviève; Piazzesi, Chiara; Pirotte, Magaly (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; approches et analyses; discipline; intersectionnalité; pratiques féministes; pédagogie; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; santé sexuelle; thématiques; éducation

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques

Boundaried caring and gendered emotion management in hospice work - Cain, Cindy L. (Gender, Work and Organization, 2017)
Caring work, which is premised on caring for and caring about recipients, involves a great deal of emotion management. Feeling rules shape expectations about emotion management and are informally shared through workers’ narratives about quality work. Using qualitative data from hospice workers in the southwestern US, I find that narratives of quality within hospice include emotion-management skills such as listening, truly caring, keeping calm and maintaining boundaries. Through an analysis of how workers discuss and map skills onto individual women and men co-workers, this article highlights two gendered patterns. First, even when women and men are thought to share high-quality skills, the ways these skills are described reinforce naturalistic understandings of gender. Second, men are seen to hold a broad range of emotion-management skills, but women are not described as holding the most important emotion-management skill: keeping boundaries. Understanding this differential application of emotion-management skills helps us to understand how gender and gender inequality are reproduced within caring work. © 2017 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; intersectionnalité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; soins palliatifs; systèmes d'oppressions; thématiques; travail; travail du care; travailleureuses de la santé; émotions; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

A visual analysis of gender bias in contemporary anatomy textbooks - Parker, Rhiannon; Larkin, Theresa; Cockburn, Jon (Social Science & Medicine, 2017)
Les recherches empiriques ont établi un lien entre les préjugés sexistes dans l’enseignement médical et les attitudes et comportements négatifs des prestataires de soins de santé. Pourtant, cela fait plus de 20 ans que les recherches n’ont pas examiné dans quelle mesure les femmes et les hommes sont représentés de manière égale dans les manuels d’anatomie . En outre, les recherches antérieures n’ont pas exploré au-delà de la quantité de représentation pour examiner également les stéréotypes visuels de genre et, à la lumière des avancées théoriques dans le domaine de la recherche intersectionnelle, la relation entre les représentations du genre et les représentations de l’ethnicité, du type de corps, de la santé et de l’âge. Cette étude visait à déterminer l’existence et la représentation des préjugés sexistes dans les principaux manuels d’anatomie utilisés dans les écoles de médecine australiennes. Une analyse systématique du contenu visuel a été menée sur 6044 images dans lesquelles le sexe/genre pouvait être identifié, provenant de 17 principaux manuels d’anatomie publiés entre 2008 et 2013. Une analyse de contenu plus approfondie a été réalisée sur les 521 images narratives, qui représentent une histoire en cours, trouvées dans les mêmes manuels. Les résultats indiquent que la représentation du genre dans les images des manuels d’anatomie reste majoritairement masculine, sauf dans les sections spécifiques au sexe. En outre, d’autres formes de biais ont été constatées dans : la visualisation d’émotions, de rôles et de contextes stéréotypés en fonction du sexe ; le manque de diversité ethnique, d’âge et de type corporel ; et dans l’adhésion presque totale à une conception binaire sexe/genre. Malgré une attention accrue portée aux questions de genre en médecine, la représentation visuelle du genre dans les programmes médicaux continue d’être biaisée. La construction biaisée du genre dans les manuels d’anatomie conçus pour l’enseignement médical fournit aux futurs prestataires de soins de santé des informations inadéquates et irréalistes sur les patients.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; australie; corps; discous dominant; intersectionnalité; livres d'anatomie; océanie; projet charge mentale; périodes historiques; racisme; représentation des corps; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Vote, ovocytes et cosmétiques. Les trois jalons identitaires du recours au genre dans la recherche sur les cellules souches en Californie - Thompson, Charis; Sofio, Séverine (Cahiers du Genre, 2014)
Cet article explore les trois jalons identitaires du recours au genre [punctuated gendering] dans la recherche biomédicale sur les cellules souches en Californie. J’y défends l’idée selon laquelle le développement de ce secteur a eu besoin des femmes à trois reprises, mais pas de toutes les femmes à chaque fois. En d’autres termes, suivant les étapes que franchissait le développement de l’innovation autour des cellules souches, les femmes ont été sollicitées en fonction d’une perception du genre à chaque fois différente. Ainsi, il a d’abord fallu faire appel à elles en tant que citoyennes, au croisement des rapports de sexe, de race et de classe ; on a ensuite eu besoin d’elles en tant que corps biologiques ; elles ont, enfin, été sollicitées en tant que consommatrices. Le but de ce triple recours aux femmes selon des identités de genre à chaque fois spécifiques, fut d’abord d’attirer des capitaux publics et privés dans ce secteur, une fois le soutien de l’état californien garanti ; puis d’assurer l’approvisionnement de la recherche en morceaux de corps humain ; et enfin, de permettre le développement de l’économie autour de l’innovation sur les cellules souches. Cet article s’appuie sur mes précédents travaux sur la biomédicalisation et la marchandisation de la reproduction, mais il s’inscrit également dans la perspective des théories de la division sexuée du travail, et de la construction sociale du genre par la publicité et la consommation. Au croisement de ces logiques, l’innovation biomédicale apparaît donc comme un espace privilégié pour étudier le genre comme répertoire identitaire dynamique, à travers une mise en œuvre concrète de l’idée d’intersectionnalité.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; intersectionnalité; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Vieillissement réussi : perception des femmes aînées immigrantes de l’Afrique noire à Montréal - Noubicier, Agnès Florette; Charpentier, Michèle (Santé mentale au Québec, 2013)
Le présent article s’intéresse aux femmes aînées des communautés ethnoculturelles de l’Afrique noire. Il a pour but de présenter le sens qu’elles donnent au « vieillissement réussi » dans leur pays d’accueil, et de mettre en évidence les facteurs qu’elles considèrent comme essentiels pour expérimenter « un maximum de satisfaction et de bonheur » au cours de cette étape de leur vie. Il s’appuie sur une étude qualitative exploratoire menée auprès de sept femmes âgées de 65 à 77 ans qui ont immigré au Québec alors qu’elles avaient plus de 50 ans. L’étude met en relief des femmes aux identités multiples et aux vieillissements différentiels, pour qui le « vieillissement réussi » est tributaire de leur implication dans la famille et dans la société, de la foi et de l’autonomie financière. L’analyse des résultats sous un angle intersectionnel permet aussi de noter que les femmes aînées immigrantes de l’Afrique noire connaissent des difficultés en raison de l’entrecroisement des effets dus à leur âge, leur appartenance ethnique et leur genre, avec d’autres aspects liés à leur identité tels que la culture, la langue, le sexe, le parcours migratoire. Une multitude d’obstacles jonchent alors leur processus de vieillissement et influent sur leur conception du « vieillissement réussi
Keywords: 2000 à aujourd'hui; accomplissement; afrique; afrique noire; amériques; approches et analyses; cours; discipline; femmes aînées; femmes immigrantes; intersectionnalité; périodes historiques; québec; récits de vie; régions géographiques; santé; santé mentale; sciences humaines; soc1061; sociologie; thématiques; travail social; vieillissement

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

United in anger: a history of ACT UP - Hubbard, Jim; Schulman, Sarah; ACT UP Oral History Project; United in Anger, Inc (United in Anger, Inc., 2012)
"A unique feature-length documentary that combines startling archival footage that puts the audience on the ground with the activists and the remarkably insightful interviews from the ACT UP Oral History Project to explore ACT UP (the AIDS Coalition to Unleash Power) from a grassroots perspective - how a small group of men and women of all races and classes, came together to change the world and save each other's lives."
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; act up; amériques; approches et analyses; cinéma; communication; cours; discipline; documentaire; film; intersectionnalité; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; états-unis

Les pratiques féminismes - Institut de recherches et d'études féministes (FéminÉtudes, 2012)
Ce numéro de 2012 illustre les pratiques féministes entre engagements, luttes et théories. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; féminétudes; genre; identités LGBTQIA2+; intersectionnalité; intervention féministe; périodes historiques; queer; québec; ressource en ligne; régions géographiques; santé; santé mentale; sexualité; thématiques

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale - Larochelle, Émilie (2010)
Les femmes handicapées constituent un groupe de la population particulièrement vulnérable à la violence conjugale. En effet, elles risqueraient davantage que les autres femmes d’être victimes de violence de la part de leur conjoint et subiraient des formes plus sévères de violence (Brownridge 2006). Elles rapporteraient également de plus longues périodes d’abus (Nosek et autres 2001a). Pourtant, peu de ressources spécialisées en matière de violence conjugale leur sont accessibles, et les études sur l’accessibilité de ces ressources ainsi que sur la violence conjugale à l’égard des femmes handicapées se font rares. C’est dans ce contexte que l’Office des personnes handicapées du Québec (l’Office) et le ministère de la Santé et des Services sociaux (MSSS) se sont engagés à documenter la problématique de la violence conjugale envers les femmes handicapées dans le cadre du Plan d’action gouvernemental 2004-2009 en matière de violence conjugale (Québec 2004). Afin de remplir cet engagement, l’Office, en partenariat avec le MSSS, a entrepris en avril 2008 le projet intitulé Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale. Ce projet vise à : 1. Documenter la problématique de la violence conjugale envers les femmes handicapées. 2. Évaluer les besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale par le réseau de la santé et des services sociaux et les maisons d’hébergement. 3. Formuler des recommandations visant la prévention de la violence conjugale auprès des femmes handicapées ainsi que l’adaptation des services aux réalités particulières vécues par celles-ci. Ce projet d’évaluation, par ses résultats et ses recommandations, contribue également à répondre à l’une des priorités d’intervention de la politique gouvernementale À part entière : pour un véritable exercice du droit à l’égalité, soit agir contre toute forme d’exploitation, de violence et de maltraitance (Québec 2009 : 31). Rappelons que cette politique a été adoptée le 4 juin 2009 par le gouvernement du Québec et a pour but d’accroître, sur une période de dix ans, la participation sociale des personnes handicapées.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; amériques; approches et analyses; canada; care; cours; discipline; intersectionnalité; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; thématiques; travail social

A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Abused women and survivor therapy - Walker, Lenore E. (American Psychological Association, 2006)
Dans ce manuel de traitement de pointe, Lenore E. A. Walker soutient que les psychothérapies traditionnelles pour les victimes de traumatismes ont été insuffisantes pour traiter les femmes maltraitées. Alors que le problème de la violence à l'égard des femmes continue de tourmenter la société, couvrant tous les secteurs démographiques, Walker décrit des modifications essentielles à la pratique traditionnelle qui permettront aux praticiens de travailler plus efficacement avec les femmes victimes de violence. Ces modifications aboutissent à une compilation intégrée des stratégies d'évaluation et d'intervention les plus réussies, appelées « thérapie de survivant ». La thérapie des femmes maltraitées et des survivants discute des principales formes de violence subies par les femmes : viol et agression sexuelle, coups de feu, abus sexuels commis par des thérapeutes et discrimination/harcèlement sexuel sur le lieu de travail. Walker examine les effets du sexe, de la race, de l'ethnicité, de la culture et de l'orientation sexuelle sur chaque forme d'abus ; discute des considérations cliniques et des approches de traitement ; évalue les instruments d'évaluation couramment utilisés ; et analyse les problèmes médico-légaux dans les cas impliquant la violence contre les femmes. Walker soutient que les modèles de traitement réussis doivent tenir compte de l'impact spécifique des diverses formes d'abus, de la réponse psychologique unique de l'individu au monde, de l'impact de la socialisation traditionnelle des femmes et des hommes, et du transfert de thérapeutes et du contre-transfert. Ces considérations peuvent être appliquées au cours d'une thérapie qui cherche à réautonomiser les femmes maltraitées en les aidant à retrouver leur estime de soi, à rétablir des relations saines et à retrouver un sentiment de contrôle et de choix dans leur vie. La thérapie des femmes maltraitées et des survivants aide les praticien.nes nouvellement formé.e.s ainsi que le praticien.ne expérimenté.e à identifier, évaluer et traiter les femmes qui ont été maltraitées physiquement, sexuellement ou psychologiquement.
Keywords: approches et analyses; cours; discipline; intersectionnalité; psychologie; santé; santé mentale; sciences humaines; thématiques; traumatismes; trs3500; violences; violences conjugales; violences sexuelles

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Les femmes autochtones au Canada : profil statistique d'après le recensement de 2006 - Affaires autochtones et développement du Nord Canada (2002)
Sommaire : points saillants de la situation des femmes autochtones au Canada. Structure de la population et lieu de résidence : •• En 2006, les femmes autochtones en Ontario représentaient environ 11 % de l’ensemble de la population d’identité autochtone. 31 % des femmes autochtones vivaient dans les provinces de l’Ouest (Manitoba, Saskatchewan, Alberta et Colombie‑Britannique). •• En 2006, l’âge médian de la population autochtone était de 27 ans, contre 40 ans pour la population non autochtone, une différence de 13 ans. Les résultats de l’étude révèlent que chez les Indiens inscrits vivant dans les réserves, un peu plus de femmes (44 %) que d’hommes (35 %) étaient âgés de 19 ans et moins. En comparaison, le pourcentage des Indiens inscrits vivant hors réserve âgés de 19 ans et moins était un peu plus élevé tant chez les femmes (45 %) que chez les hommes (43 %). De plus, de tous les groupes d’identité autochtone, c’est chez la population inuite féminine (49 %) et masculine (46 %) que se trouvait la proportion la plus importante des 19 ans et moins. •• La population féminine autochtone vieillit, quoique à un rythme plus lent que la population féminine non autochtone. En 2006, les femmes de 60 ans et plus représentaient plus de 7 % de l’ensemble de la population d’identité autochtone. Utilisation et connaissance des langues •• Les résultats de l’étude révèlent que la majorité des femmes autochtones, soit 73 %, ont appris l’anglais comme langue maternelle, tandis que seulement 16 % ont d’abord appris une langue autochtone et 8 %, le français. La proportion de filles et de femmes autochtones dont la langue maternelle est une langue autochtone (langue amérindienne ou inuktitut) est relativement faible dans les groupes d’âge plus jeunes, et plus élevée dans les groupes d’âge plus âgés. L’anglais prend donc plus d’importance que les langues autochtones et le français au fil du temps. •• La proportion de la population de langue maternelle autochtone est plus élevée chez les Inuites. Un plus grand nombre de femmes inuites de tous les groupes d’âge, soit 65 %, indiquent que l’inuktitut est leur langue maternelle, contre 32 % pour l’anglais. Chez 28 % des Indiennes inscrites, la langue maternelle est une langue autochtone; la proportion est beaucoup plus faible chez les Métisses, à 3 %. •• La vaste majorité (75 %) des Autochtones parlent principalement l’anglais à la maison, alors que 16 % parlent une langue autochtone et 5 %, le français. En outre, 29 % des membres des Premières nations affirment qu’ils peuvent parler une langue autochtone suffisamment bien pour tenir une conversation. La proportion est cependant beaucoup plus élevée chez les membres des Premières nations vivant dans les réserves. En 2006, la moitié des membres des Premières nations vivant dans les réserves (51 %) pouvaient s’exprimer dans une langue autochtone, contre 12 % de ceux qui vivaient hors réserve. Les langues des Premières nations les plus répandues en 2006 étaient le cri (87 285), l’ojibway (30 255), l’oji‑cri (12 435) et le montagnais‑naskapi (11 080).
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; démographie; famille; femmes* autochtones; géographie; histoire et politique; intersectionnalité; langue; langues autochtones; maternité; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; thématiques; transmissions; éducation; étude démographique

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap

Not in our genes: biology, ideology, and human nature - Lewontin, Richard C.; Rose, Steven P. R.; Kamin, Leon J. (Pantheon Books, 1984)
Keywords: approches et analyses; biologie; corps; cours; discipline; génétique; intersectionnalité; justice sociale; lit4700; premier cycle; racisme; santé; sciences; sexisme; systèmes d'oppressions; thématiques

Avortement : un pays pas comme les autres - Harrison-Julien, Pasquale
L’avortement au Canada est une réalité complexe et souvent méconnue. De la Gaspésie au Nunavik, en passant par les provinces de l'Atlantique et les grandes villes, la série balado Avortement : un pays pas comme les autres met en lumière les disparités régionales et les obstacles rencontrés par les Canadiennes désirant avoir recours à ce soin de santé. La journaliste Pasquale Harrison-Julien aborde des sujets délicats tels que les avortements après le premier trimestre, les pressions culturelles et familiales, et les implications politiques et sociales des lois sur l'avortement. À travers des témoignages poignants et des entretiens avec des experts, des militants et des médecins, découvrez les histoires de femmes qui ont dû naviguer dans un système de santé inégal pour exercer leur droit dans ce balado essentiel pour comprendre les enjeux actuels et futurs de la santé reproductive au Canada.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; avortement; canada; communication; cours; discipline; droits des femmes*; intersectionnalité; journalisme; justice reproductive; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; santé; sexisme; système colonial; systèmes d'oppressions; thématiques

Contexte de vulnérabilité : femmes handicapées | INSPQ - Levasseur, Karine (Institut national de santé publique du Québec)
Keywords: EDI; amériques; approches et analyses; canada; capacitisme; care; cours; discipline; intersectionnalité; inégalités; justice sociale; premier cycle; québec; ressource en ligne; régions géographiques; santé; sex1920; sexisme; systèmes d'oppressions; thématiques